Green‐light emission through energy transfer from Ce3+ to Tb3+ ions in the Li2SO4–Al2(SO4)3 system. (19th February 2019) - Yerpude, M.M.; Nair, Govind B.; Dhoble, S.J.
Abstract: An energy transfer process from Ce 3+ to Tb 3+ ions was successfully achieved in a Li2 SO4 –Al2 (SO4 )3 mixed‐sulphate system. A wet‐chemical synthesis was employed to prepare the Li2 SO4 –Al2 (SO4 )3 system by doping Ce 3+ and Tb 3+ ions individually as well as collectively. The phases were identified using X‐ray diffraction studies. The as‐prepared samples were characterized by FT‐IR and photoluminescence measurements. Green‐light emission was exhibited by Ce 3+, Tb 3+ co‐doped Li2 SO4 –Al2 (SO4 )3 system, thus, indicating its potential as a material for display devices or in the lamp industry.